Penerapan UU ITE (Informasi dan Transaksi Elektronik) dan UU Perlindungan Konsumen pada Kasus Jual Beli Jasa Review Palsu - Rahmansyah Fadli Alkarim Rambe; Syahdan Ivander Bayu; Salsabila Sagala (Journal on Education, 2023)
This research examines the application of the Information and Electronic Transactions Law (UU ITE) and the Consumer Protection Law in the context of fake review service buying and selling transactions. By using case analysis methods and legislative reviews, this research aims to explore the impact of law and consumer protection on this practice. The background involves concerns over the integrity of consumer information and the illegal use of fake reviews in online businesses. Research methods include in-depth analysis of applicable regulations and related case studies. The research findings provide an in-depth understanding of the legal challenges and consumer protection in the context of buying and selling fake review services. The conclusion highlights the need for coordination between the ITE Law and the Consumer Protection Law as well as increased regulation to maintain the integrity of digital markets. This research contributes to better practical understanding and policy development regarding consumer protection and law in the digital environment